Somalia Economic Update, August 2018 : Rapid Growth in Mobile Money - Stability or Vulnerability? - Randa, John; World Bank (World Bank, Washington, DC, 2018)
Somalia’s economy grew by 2.3 percent in 2017. The economy remains vulnerable to recurrent shocks. Between 2013 and 2017, real annual GDP growth averaged 2.5 percent. Growth occurred despite adverse weather conditions that severely reduced agricultural output in late 2016 and early 2017. For Somalia to enhance and sustain economic growth and escape chronic poverty, it must increase its resilience to shocks. Growth recovery is set to continue beyond 2018, lifted by gains from ongoing reforms as well as improved security. Rising domestic demand, remittances, and donor inflows and consolidation of peace and security are expected to drive growth in 2019–20. Achieving higher growth will require acceleration of structural reforms, particularly in three areas: fiscal policy and public financial management, provision of basic services (to promote human development and inclusion), and improved resilience to weather shocks particularly in the agriculture sector. Mobile money is an essential part of Somalia’s economic ecosystem. Almost three-quarters of the population aged 16 and above use mobile money on a regular basis. It is now the main transaction instrument used by both individuals and businesses across the country: presenting an opportunity to increase access to finance, spur inclusive growth, and promote resilient communities. However, with increasing dependence on mobile money as a medium of exchange comes increased vulnerabilities.